Optimization of Crude Palm Oil Fund to Support Smallholder Oil Palm Replanting in Reducing Deforestation in Indonesia - Nurfatriani, F.; Ramawati; Sari, G.K.; Komarudin, Heru (MDPI, 2019)
Smallholders play a significant role in the Indonesian palm oil industry. They cultivate more than 40% of the total plantation area, and their production contributes to the national revenue. However, despite their significant role, smallholders continue to face crop management, financial and environmental challenges. The fact that some smallholder plantations are illegally located in state forestland poses challenges for smallholders as regards getting access to finance, improving yields, and obtaining sustainable certification. Government policy on the collection of levies from exported crude palm oil (CPO fund) and its derivative products provides smallholders the opportunity to replant and support their sustainable practices, thereby reducing deforestation. This paper discusses how fiscal incentives of the CPO fund may have been optimized to prioritize these outcomes. We should prioritize the use of the fund not only to support smallholder replanting, but also to clarify their land tenure rights, so that they could get access to sustainable certification and financial institutions. It is also recommended that funds be allocated to subsidize loan interest to the bank and build productive capital during the grace period. These efforts have to be accompanied by building and improving smallholder databases and strengthening local government.